Expedient Synthesis of the Proposed Structure of Cryptoconcatone H Exploiting Hidden Symmetry - Ford, Hannah G.; Hastry, Emma C.; Choi, Joshua B.; Terranova, Christopher J.; Quinn, Kevin J. (Synlett, 2022)
Synthesis of the originally assigned structure of the styryl tetrahydropyranol-dihydropyranone natural product cryptoconcatone H from C2-symmetric (±)-1,8-nonadiene-4,6-diol is reported. Desymmetrization by Mitsunobu reaction with crotonic acid established the requisite inter-ring stereochemical relationship and was followed by a highly diastereoselective Re2O7-catalyzed Prins cyclization with cinnamaldehyde to construct the 2,4,6-cis-tetrahydropyranol ring. Ring-closing metathesis resulted in formation of the dihydropyranone ring and completed the synthesis in three steps and 32% overall yield. The brevity of the synthesis is the result of the recognition of hidden, inter-ring symmetry in the target and the ensuing choice of an appropriately symmetric diol as our starting material.
Keywords: cryptoconcatone H; total synthesis; hidden symmetry; Mitsunobu reaction; Prins cyclization; ring-closing metathesis